KETENTUAN HUKUM PERLINDUNGAN HAK ANAK JALANAN BIDANG PENDIDIKAN - Sofyan, Andi Muhammad; Tenripadang, Andi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: National Education System, explains that education is a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have state power, self-control, personality of intelligence, noble character, as well as skills needed him, society, nation and country. Legal provisions for the protection of the rights of street children are legal provisions both at the level of laws, provincial and district / municipal regulations governing the protection, survival value, development, maintenance, welfare, education, physical health, moral social and mental spiritual. Legal provisions on the education of children should have a harmonious regulation both at the level of regulations issued by the government, provincial and municipal governments and districts that contain provisions both in terms of responsibility, to the involvement of the community in managing education based on the basic ideals of the Republic Indonesia